Digital Agency and Counter-Narratives in Religious Mediation: Feminist Niqab-Wearing Women on Instagram @cadargarislucu - Nanang Mizwar Hasyim; Mahbub Ghozali (An-Nida', 2026)
Research concerning veiled women on social media has predominantly concentrated on issues of identity representation and religious stigma, whereas digital mediation practices as a form of community agency have received comparatively limited scholarly attention. This study seeks to examine the mediation practices employed by the Instagram community @cadargarislucu in the construction of the religious identity of veiled women within Indonesia’s digital public sphere. Employing a qualitative methodology, the research analyses thirteen Instagram posts, including images, videos, and carousels, through content analysis and critical discourse analysis. The analytical process was conducted in two phases: initially identifying themes and message patterns, followed by an examination of meaning construction  within the interplay of text, discursive practices, and social context. The study’s theoretical framework integrates Stewart M. Hoover’s theory of religious mediation with Norman Fairclough’s critical discourse analysis. The findings reveal four interrelated forms of mediation practices: firstly, the appropriation of viral language to construct communicative religious-feminist narratives; secondly, the utilisation of contemporary issues and digital technologies as sources of symbolic culture; thirdly, the negotiation of meaning through the articulation of value-based attitudes; and fourthly, the hybridisation of religious-feminist identity as a  reinterpretation of the veil (cadar). These practices illustrate how digital agency facilitates the transformation of the veil from a stigmatized symbol into one representing empowerment, inclusivity, and religious moderation. The results underscore the centrality of community agency in the production of religious meaning within digital spaces and contribute to the advancement of counter-narrative strategies for minority groups  confronting dominant discourses on social media.